Determination of parameters for the damage mechanics approach to ductile fracture based on a single fracture mechanics test: - Coppejans, O.J.; Walters, C.L. (2017)
The local approach to modelling ductile tearing is a useful technique to give insight into fracture mechanics. However, applications of the local approach have been stymied by the high cost of finding the parameters that characterize it because of the number of specimens and expensive post-processing that the testing requires. In this paper, a novel iterative method to extract a failure locus from one Crack Tip Opening Displacement (CTOD) specimen is presented. Material points fail under various different stress states in a CTOD specimen, so many different points on the failure locus can be found through thoughtful post-processing in FEA. A phenomological ductile failure locus is fitted through the stress triaxiality, Lode angle, and plastic strains that cause failure at material points in the CTOD test. Simulating a CTOD test with a different aspect ratio has shown that the failure locus found by this method can be predictive, giving both accurate force versus Crack Mouth Opening Displacement (CMOD) curves and realistic fracture surfaces featuring separate tunnelling and shear lips.